Netprov Networked Improvised Literature for the Classroom and Beyond - Wittig, Rob (Amherst College Press, 2022)
Netprov is an emerging interdisciplinary digital art form that offers a literature-based "show" of insightful, healing satire that is as deep as the novels of the past. This accessible history of Netprov emerges out of an ongoing conversation about the changing roles and power dynamics of author and reader in an age of real-time interactivity. Rob Wittig describes a literary genre in which all the world is a platform and all participants are players. Beyond serving as a history of the genre, this book includes tips and examples to help those new to the genre teach and create netprovs.